National innovative ecosystem as a platform for the country’s social-economic development - Ya. V. Danilina; M. A. Rybachuk (Russian Journal of Economics and Law)
Objective: to improve approaches to forming a strategy for the development of a national innovation system.Methods: the work uses a set of methods and approaches, such as the system economic theory, the space-time analysis andsynthesis.Results: the results of the implementation of the Strategy of Innovative Development of the Russian Federation until 2020 was analyzed, which enabled to formulate conclusions about the low efficiency of the results of its implementation. The essence of the national innovation ecosystem and the approaches to its formation were determined. The necessity of applying the ecosystem approach in the formation of the national innovation system is substantiated, recommendations on the system economic theory application in building an integrated national innovation ecosystem are presented. An approach to the organization of the national innovation system as a quadruple helix is proposed, which will ensure the connectivity of its components. The analysis of the possibilities of using digital technologies to develop innovative connections based on ecosystem principles is carried out.Scientific novelty: it consists in the application of systemic economic theory and ecosystem principles that allow taking into account the institutional and socio-economic conditions specific to Russia for the development of the national innovation system.Practical significance: the research results presented in the article can be used to create a strategy for the innovative development of the Russian Federation for the future, as well as for the development of the national innovation system as a whole.